2005
DOI: 10.1021/ac0484530
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Ephedrine Alkaloids in Dietary Supplement Standard Reference Materials

Abstract: /npsi/ctrl?action=rtdoc&an=5764712&lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?action=rtdoc&an=5764712&lang=fr READ THESE TERMS AND CONDITIONS CAREFULLY BEFORE USING THIS WEBSITE.http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en Vous avez des questions? Nous pouvons vous aider. Pour communiquer directement avec un auteur, consultez la première page de la revue dans laquelle son article a été publié afin de trouver ses coordonnées. Si vous n'arrivez pas à les repérer, communiqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 15 publications
5
41
0
Order By: Relevance
“…1). An overview of different methodologies (LC-UV, LC-MS, LC-MS-MS and CE) for the analysis of Ephedra alkaloids was presented by Sander et al [19], whereas Phinney et al [20] compared the effects of different cyclodextrins on this separation problem. They concluded that the combination of S-X-CD and DM-X-CD will be most suitable as additive.…”
Section: Alkaloidsmentioning
confidence: 99%
“…1). An overview of different methodologies (LC-UV, LC-MS, LC-MS-MS and CE) for the analysis of Ephedra alkaloids was presented by Sander et al [19], whereas Phinney et al [20] compared the effects of different cyclodextrins on this separation problem. They concluded that the combination of S-X-CD and DM-X-CD will be most suitable as additive.…”
Section: Alkaloidsmentioning
confidence: 99%
“…Recently, the National Institute of Standards and Technology (NIST) issued a suite of five ephedra-containing dietary supplements standard reference materials (SRMs) with certified values for ephedrine alkaloids, synephrine, and caffeine [7]. The materials constitute various types of natural, extracted, and processed sample matrices.…”
Section: (1r2s)-(-)-ephedrine [(-)-Ep] (1s2s)-(1)-pseudoephedrine mentioning
confidence: 99%
“…Hence, accurate and sensitive analysis of such samples is of significant challenge to analytical chemists. Sandar et al published certified values of six ephedrine alkaloids of interest [(-)-EP, (1)-c-EP, (-)-Nor-EP, (1)-Nor-c-EP, (-)-Me-EP, and (1)-Me-c-EP] which were independently measured by different laboratories using several methods such as LC-UV, LC-MS, LC-MS/MS and CE [7]. In addition, Phinney and co-workers developed three chiral CE-UV methods using either single or dual CD-based chiral selector systems for the analysis of a suite of five SRMs with the aim of achieving enantioselective separations [8].…”
Section: (1r2s)-(-)-ephedrine [(-)-Ep] (1s2s)-(1)-pseudoephedrine mentioning
confidence: 99%
“…1. Increasing concern on the part of both consumers and regulatory agencies as to the safety of ephedra alkaloids has led to the development of several methods to measure ME by GC (Van Eenoo et al, 2001) and CE Sander et al, 2005) or PSE by GC (Lee et al, 2006), HPLC (Aljazaf et al, 2003;Ishida et al, 2008;Karakus et al, 2008;Ma et al, 2007) and CE . The rapid and sensitive determination and pharmacokinetics study of ME and PSE are important in biochemical and clinical analysis.…”
Section: Introductionmentioning
confidence: 99%